Symptomology, Outcomes and Risk Factors of Acute Coronary Syndrome Presentations without Cardiac Chest Pain: A Scoping Review - Meriem Perona; Amanda Cooklin; Christopher Thorpe; Peter O’Meara; Muhammad Aziz Rahman (European Cardiology Review)
For patients experiencing acute coronary syndrome, early symptom recognition is paramount; this is challenging without chest pain presentation. The aims of this scoping review were to collate definitions, proportions, symptoms, risk factors and outcomes for presentations without cardiac chest pain. Full-text peer reviewed articles covering acute coronary syndrome symptoms without cardiac chest pain were included. MEDLINE, CINAHL, Scopus and Embase were systematically searched from 2000 to April 2023 with adult and English limiters; 41 articles were selected from 2,954. Dyspnoea was the most reported (n=39) and most prevalent symptom (11.6–72%). Neurological symptoms, fatigue/weakness, nausea/vomiting, atypical chest pain and diaphoresis were also common. Advancing age appeared independently associated with presentations without cardiac chest pain; however, findings were mixed regarding other risk factors (sex and diabetes). Patients without cardiac chest pain had worse outcomes: increased mortality, morbidity, greater prehospital and intervention delays and suboptimal use of guideline driven care. There is a need for structured data collection, analysis and interpretation.